1999
DOI: 10.1128/aac.43.10.2430
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of TEM- and PSE-Type β-Lactamases among Amoxicillin-Resistant Salmonella spp. Isolated in France

Abstract: A survey conducted between 1987 and 1994 at the University Hospital of Besançon, France, demonstrated a dramatic increase (from 0 to 42.5%) in the prevalence of amoxicillin resistance amongSalmonella spp. Of the 96 resistant isolates collected during this period (including 77 Typhimurium), 54 were found to produce TEM-1 β-lactamase, 40 produced PSE-1 (equivalent to CARB-2), one produced PSE-1 plus TEM-2, and one produced OXA-1 in isoelectric focusing and DNA hybridization experiments. Plasmids coding for thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 43 publications
4
10
2
Order By: Relevance
“…The fact that this PCR product was observed in isolates 49 and 50 of phenotype C S T R indicated that the flo ST gene also conferred resistance to tetracycline, which is in agreement with literature data [7,13]. In total, a resistance plasmid conferring multiresistance to chloramphenicol, streptomycin, sulphonamide and tetracycline described elsewhere in DT 104 isolates [5,6,23,27] has been found in this study, in addition to resistance mediated by ␤-lactamase production.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The fact that this PCR product was observed in isolates 49 and 50 of phenotype C S T R indicated that the flo ST gene also conferred resistance to tetracycline, which is in agreement with literature data [7,13]. In total, a resistance plasmid conferring multiresistance to chloramphenicol, streptomycin, sulphonamide and tetracycline described elsewhere in DT 104 isolates [5,6,23,27] has been found in this study, in addition to resistance mediated by ␤-lactamase production.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in line with those observed by Gallardo et al [15] who found 52% TEM-1, 39% PSE-1 and 8% OXA-1 ␤-lactamase-producing strains. The percentages of our isolates producing either PSE-1 or TEM-1 was quite similar to those found by Llanes et al [23] with respect to PSE-1 (48% versus 42.5%) and TEM-1 (44% versus 57.4%). From our results, it seems clear that multiresistant S. Typhimurium isolates presented various genotypes and produced various plasmid-mediated ␤-lactamases.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This phenotype has already been attributed in Salmonella to the simultaneous production of TEM-1 and PSE-1 ␤-lactamases [10,20]. By using PCR primers specific for the pse-1 gene (encoding PSE-1 ␤-lactamase) we were able to amplify the expected DNA fragment from 17 Salmonella strains (two amoxicillin-clavulanate-resistant strains, 10 moderately susceptible and five susceptible).…”
Section: Identification Of Antibiotic Resistance Genesmentioning
confidence: 95%